Spectroastrometry and Reverberation Mapping of Active Galactic Nuclei. I. The Hβ Broad-line Region Structure and Black Hole Masses of Five Quasars - Yan-Rong Li; Chen Hu; Zhu-Heng Yao; Yong-Jie Chen; Hua-Rui Bai; Sen Yang; Pu Du; Feng-Na Fang; Yi-Xin Fu; Jun-Rong Liu; Yue-Chang Peng; Yu-Yang Songsheng; et al. (The Astrophysical Journal, 2024)
We conduct a reverberation mapping (RM) campaign to spectroscopically monitor a sample of selected bright active galactic nuclei with large anticipated broad-line region (BLR) sizes adequate for spectroastrometric (SA) observations by the GRAVITY instrument on the Very Large Telescope Interferometer. We report the first results for five objects, IC 4329A, Mrk 335, Mrk 509, Mrk 1239, and PDS 456, among which Mrk 1239 and PDS 456 are for the first time spectroscopically monitored. We obtain multiyear monitoring data and perform multicomponent spectral decomposition to extract the broad H β profiles. We detect significant time lags between the H β and continuum variations, generally obeying the previously established BLR size–luminosity relation. Velocity-resolved H β time lags illustrate diverse, possibly evolving, BLR kinematics. We further measure the H β line widths from mean and rms spectra and the resulting virial products show good consistency among different observing seasons. Adopting a unity virial factor and the FWHM of the broad H β line from the mean spectra as a measure of velocity, the obtained black hole masses averaged over seasons are $logM_{\bullet }/M_{\odot }={8.02}_{-0.14}^{+0.09}$ , ${6.92}_{-0.12}^{+0.12}$ , ${8.01}_{-0.25}^{+0.16}$ , ${7.44}_{-0.14}^{+0.13}$ , and ${8.59}_{-0.11}^{+0.07}$ for the five objects, respectively. Black hole mass estimations using other line width measures are also reported. For objects with previous RM campaigns, our mass estimates are in agreement with earlier results. In a companion paper, we will employ BLR dynamical modeling to directly infer the black hole mass and thereby determine the virial factors.